COMPARATIVE CUSTOMS VALUATION METHODOLOGY IN THE CONTEXT OF THE EUROPEAN COMMISSION’S UPDATED GUIDANCE - RUSAK, Denis (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the details of customs value calculations and examples from the practice of EU importers in the context of the updated guidance of the European Commission on customs valuation and explains typical methodologies for calculating customs value and customs payments, special cases of determining the final customs valuation of imported goods under the conditions of application concerning transfer pricing, special cases of determination of customs value in the context of court decisions in the EU countries. The modern scientific studies of the adaptation’s process of national customs legislation to international norms, rules and standards, which must be considered in accordance with international customs and legal norms and in accordance with European standards. The article also examines the forms of customs value adjustment in the context of transfer pricing and the impact of court decisions on the future common European practice and legislation on customs value.